Defect Chemistry: Pushing the Study of Point Defects in Thin Film Ferrites to Low Temperatures Using In Situ Ellipsometry (Adv. Mater. Interfaces 6/2021). Issue 6 (23rd March 2021) - Tang, Yunqing; Chiabrera, Francesco; Morata, Alex; Garbayo, Iñigo; Alayo, Nerea; Tarancón, Albert
Abstract : The defect chemistry of La1− x Sr x FeO3−δ (LSF) thin films is unveiled for intermediate‐to‐low temperature range using a novel in situ ellipsometry approach. The evolution of the concentration of holes in the LSF thin films with oxygen partial pressure and temperature is obtained. This technique pushes the limits for tracking the defect chemistry in LSF thin films to lower temperature. More details can be found in article number 2001881 by Francesco Chiabrera, Albert Tarancón, and co‐workers.